Short-term outcome of periviable small-for-gestational-age babies: is our counseling up to date? - Lawin-O'Brien, A; Dall'Asta, A; Knight, C; Sankaran, S; Scala, C; Khalil, A; Bhide, A; Heggarty, S; Rakow, A; Pasupathy, D; Papageorghiou, A; Lees, C (Wiley, 2016)
Objective There are limited data for counseling on and management of periviable small-for-gestational-age (SGA) fetuses. We therefore aimed to investigate the short-term outcome of periviable SGA fetuses in relation to the likely underlying cause. Methods This was a retrospective study of data from three London tertiary fetal medicine centers obtained between 2000 and 2015. We included viable singleton pregnancies with a severely small fetus, defined as those with an abdominal circumference ≤ 3rd percentile, identified between 22 + 0 and 25 + 6weeks’ gestation. Data obtained included fetal biometry, presence of placental anomalies, uterine and fetal Doppler and neonatal outcome. We excluded cases with structural abnormalities, proven or suspected abnormal karyotype or genetic syndromes. Cases were classified according to the suspected underlying cause of the small fetal size into one of the following categories: uteroplacental insufficiency, evidence of placental damage with normal uterine artery Doppler, viral infection, or unclassied. Results There were 245 cases included in the study. Of these, at diagnosis of SGA, 201 (82%) were categorized as uteroplacental cause, 13 (5%) as suspected placental cause, one (0.4%) as suspected viral cause and 30 (12%) could not be assigned to any of these categories. Overall, 101 (41%) cases survived the neonatal period; 89 (36%) underwent in-utero fetal demise, 22 (9%) died neonatally and 33 (14%) pregnancies were terminated. The diagnosis-to-delivery interval was 8.1weeks in those that survived and 4.5 weeks in those that died neonatally. Conclusions Almost 90% of periviable SGA cases are associated with uteroplacental insufficiency or intraplacental damage. Survival is related to gestational age at delivery, with outcomes better than might be assumed at diagnosis and some pregnancies reaching term.